Respuesta :
Answer:
x⁻²
Step-by-step explanation:
If y = e²ˣ, y' = 2e²ˣ.
2xe²ˣ + 2e²ˣ ≠ 0
If y = x², y' = 2x.
2x² + 2x² ≠ 0
If y = x⁻², y' = -2x⁻³.
-2x⁻² + 2x⁻² = 0
The x^-2 function is a solution to the differential equation
[tex]xy ' + 2y = 0.[/tex]
We have given,
The differential equation[tex]xy ' + 2y = 0.[/tex]
What is the differential equation?
A differential equation is an equation with one or more derivatives of a function. The derivative of the function is given by dy/dx.
If [tex]y = e^{2x}, y' = 2e^{2x}.[/tex]
[tex]2xe^2x + 2e^2x[/tex]≠0
If [tex]y = x^2, y' = 2x.[/tex]
[tex]2x^2 + 2x^2[/tex]≠0
If[tex]y = x^-2, y' = -2x^-3.[/tex]
[tex]-2x^-2 + 2x^-2= 0[/tex]
Therefore, the x^-2 function is a solution to the differential equation
[tex]xy ' + 2y = 0.[/tex]
To learn more about the differential equation visit:
https://brainly.com/question/1164377
#SPJ2